Radiation Effects in Materials 2016
DOI: 10.5772/62464
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects in Polyamides

Abstract: Polyamides PAs are largely used either as engineering materials in virgin form or as composites and a component of polymer blends. Various processes have been used to modify some properties of polymers to improve their utility. For this purpose, radiation technologies present clear, one-step procedures and offer improvement to the performance of PA materials. Irradiation by accelerated electron beams, γ-rays, and accelerated protons is applied on PAs, particularly PA-, as well as PA composites. Variations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This increment in viscosity can be explained through branching in the lower doses and crosslinking at the higher. It can be observed that samples irradiated in argon show the lowest variability between recycled and virgin species, and this phenomenon is most likely linked to the randomness of the irradiation process when performed in air, as secondary oxidation reactions take place [ 17 ]. The recycled sample has a lower starting viscosity value, and the tendency is reverted at higher absorbed doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increment in viscosity can be explained through branching in the lower doses and crosslinking at the higher. It can be observed that samples irradiated in argon show the lowest variability between recycled and virgin species, and this phenomenon is most likely linked to the randomness of the irradiation process when performed in air, as secondary oxidation reactions take place [ 17 ]. The recycled sample has a lower starting viscosity value, and the tendency is reverted at higher absorbed doses.…”
Section: Resultsmentioning
confidence: 99%
“…The material presenting faster weight loss is the raw (virgin) sample irradiated at 100 kGy. It is known that scission events coexist with crosslinking under these irradiation conditions, and thus, chain rupture and polymer degradation result in chemical species that tend to decompose easily [ 17 ]. The main difference with its recycled counterpart is that crystallinity in this sample was about 20% higher; thus, bonds in the latter configuration are stronger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In every case, sensitivity coefficient values for irradiated samples were lower than for those not irradiated. Most of the radiation impact was exerted on the physical elasticity of the cable: the PA outer sheath became more rigid and less elastic due to radiation [20], leading to more cracks during handling and elongation and, therefore, to break sooner than non-irradiated samples (Figure 5). With the exception of the fibers, the standard samples, and the not irradiated V9 type, some cables broke during the test.…”
Section: Strain Sensitivity Coefficientsmentioning
confidence: 99%
“…The most widespread form of polymerization from academic and commercial perspectives is the free-radical polymerization technique which is broadly applicable to a wide range of monomers [10]. The effect of the electron accelerator and proton beam irradiation on both the mechanical and chemical properties of polyamide [11] and epoxy composites [12,13] were studied. Ahmad Anwar et al, in 2016, studied one of the space hazards affecting on polymeric materials by exposure of the polyimide to ionized and particulate radiation at a dose up to1000kGy by gamma source and evaluated its performance [14].…”
Section: Introductionmentioning
confidence: 99%